Аналіз особливостей автоматизації тестування простих та комплексних вебдодатків - Бузніков, В. Р. (ХНУРЕ, 2022)
This work is devoted to familiarization and education on the automation of testing web applications. Web application testing automation is a check of a web application for operability and detection of various errors. The tools for automating the actions of a web browser, as well as the features of testing web applications are considered. Selecting the required programming language and automation tool is considered.
Keywords: automation of testing; Web application